PENGARUH WAKTU MILLING PADA PADUAN Mg-Ca-Zn-CaH2 UNTUK APLIKASI IMPLAN[The Effects of Milling Time On Mg-Ca-Zn-CaH2 Alloys for Implant Application] - Lestari, Franciska Pramuji; T, Yudi Nugraha; Kartika, Ika; Sriyono, Bambang (Jurnal Metalurgi, 2013)
Mg-Ca-Zn alloy is metal alloys that used for metal foam implant application. This research were investigated about pre-eliminary study of metal foaming manufacturing from pure powder Mg-Ca-Zn-CaH2 with dry milling process in room temperature. The aim of the study was to study about the homogeneity and mechanic reactivity of milling the pure powder of Mg-Ca-Zn-CaH2. Milling time variation of those process were 2, 4 and 6 hours and used steel and ceramic balls mill as a crusher and stirrer media. Then powder sample which had mixed are compacted with compaction machine at 1000 KPa in cylinder dies with 25 mm in diameter. Mapping SEM qualitative analysis show that powder particle disintegrated to be smaller and homogeneity as qualitative with addition of milling time. From elastic recovery percentage shows that powder milled during 6 hours has lowest elastic recovery approximately around 43.6% XRD analyses show that binner phase MgZn and Mg2Zn were formed.